2018
DOI: 10.1016/j.neo.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Usp9x Promotes Survival in Human Pancreatic Cancer and Its Inhibition Suppresses Pancreatic Ductal Adenocarcinoma In Vivo Tumor Growth

Abstract: Usp9x has emerged as a potential therapeutic target in some hematologic malignancies and a broad range of solid tumors including brain, breast, and prostate. To examine Usp9x tumorigenicity and consequence of Usp9x inhibition in human pancreatic tumor models, we carried out gain- and loss-of-function studies using established human pancreatic tumor cell lines (PANC1 and MIAPACA2) and four spontaneously immortalized human pancreatic patient-derived tumor (PDX) cell lines. The effect of Usp9x activity inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Reduced USP9X expression confers selective growth advantage to various tumors (Schwickart et al, 2010; Pérez-Mancera et al, 2012; Peng et al, 2013; Kushwaha et al, 2015; Yang et al, 2016; Zhang et al, 2016; Toloczko et al, 2017; Khan et al, 2018; Li et al, 2018; Pal et al, 2018). Therefore, we investigated the stability of additional USP9X targets in MRXS99F fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced USP9X expression confers selective growth advantage to various tumors (Schwickart et al, 2010; Pérez-Mancera et al, 2012; Peng et al, 2013; Kushwaha et al, 2015; Yang et al, 2016; Zhang et al, 2016; Toloczko et al, 2017; Khan et al, 2018; Li et al, 2018; Pal et al, 2018). Therefore, we investigated the stability of additional USP9X targets in MRXS99F fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…The function of USP9x is cell-type specific. USP9x has been viewed as a tumor suppressor gene in colorectal and pancreatic ductal adenocarcinoma, while others reported that USP9x is an oncogene in breast cancer, glioblastoma, and leukemia (Akiyama et al, 2019;Chen et al, 2019;Khan et al, 2018a;Pal et al, 2018;Potu et al, 2017b;Zhu et al, 2018). Our results suggest that USP9x may function as an not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
“…The significant downregulation of ECT2 expression in the miR-223-3p mimic group further confirmed that miR-223-3p could regulate the expression of ECT2. The biological behavior of cancer cells is an important marker reflecting the progress and severity of cancer 2830. In order to explore how miR-223-3p and ECT2 are involved in the regulation of biological characteristics of BC cells, CCK8 and flow cytometry were used to detect the cell viability and apoptosis in each group.…”
Section: Discussionmentioning
confidence: 99%